Baseline erythrocyte sedimentation rate level predicts long-term inhibition of radiographic progression by tocilizumab: the KURAMA cohort - Ryu Watanabe; Kosaku Murakami; Toshimitsu Fujisaki; Hiromu Ito; Koichi Murata; Wataru Yamamoto; Takayuki Fujii; Hideo Onizawa; Akira Onishi; Masao Tanaka; Akio Morinobu; Motomu Hashimoto (Immunological Medicine, 2023)
AbstractThe short-term effect of tocilizumab (TCZ) on the radiographic progression of rheumatoid arthritis has been reported; however, reports on its long-term effects are scarce. In this study, we aimed to evaluate its long-term effects on joint destruction in patients who had been treated with TCZ for at least two years and for whom X-rays were available. Radiographic progression was evaluated with modified Total Sharp Score (mTSS), and structural remission was defined as the mean annual change in mTSS ≤0.5. Of the 59 patients included in this study (median age, 62 years; female, 81.4%), 34 patients (57.6%) achieved structural remission. Patients who achieved structural remission were relatively younger (59 years vs. 64 years, p = .06), had relatively higher proportion of anti-citrullinated protein antibody positivity (91.2% vs. 72.0%, p = .08), relatively lower C-reactive protein level (0.6 mg/dL vs. 2.2 mg/dL, p = .05), and significantly lower erythrocyte sedimentation rate (ESR) level (28.0 mm/h vs 65.5 mm/h, p = .003) than those who did not. Multivariate logistic regression analysis demonstrated that the baseline ESR level was significantly associated with structural remission (odds ratio, 0.98; 95% confidence interval: 0.96–0.99, p = .049). The baseline ESR level is a critical determinant of the long-term effect of TCZ on joint destruction.